Synthesis of Novel 2-Amino-benzo[de]isoquinolin-1,3-dione Derivatives - Al-Salahi, R.; Marzouk, M. (Asian Journal of Chemistry, 2014)
From a pioneer bioactive amino-benzoisoquinoline i.e. 2-amino-1H-benzo[de]isoquinolin-1,3-dione, a new series of Schiff's bases were prepared by the reaction of the active 2-amino group with a variety of aryl(hetero)aldehydes, isothiocyanides and acid anhydrides. The success of all reactions has been followed up by characterization of the synthesized target molecules through IR, Mass spectra and NMR analyses. The structural modifications were designed aiming at synthesis of valuable bioactive agents.